PERAN PEREMPUAN DALAM TIM SUKSES PASANGAN JAROT ANSORI PADA KAMPANYE PEMILIHAN KEPALA DAERAH KABUPATEN SUMBAWA TAHUN 2024 - Loya Lani Gezi Raka Siwi; Joni Firmansyah (Fakultas Ekonomi dan Manajemen, 2026)
This study aims to examine the role of women in the campaign team of the Jarot-Ansori pair in the 2024 Sumbawa Regional Head Election, including forms of involvement, driving and inhibiting factors, and their contributions to campaign effectiveness. The research is situated within the local political dynamics of Sumbawa Regency, which recorded a high voter turnout of 80.6%, with women constituting the majority of voters (50.7%), while their participation in strategic political structures remains limited.The study employs a descriptive qualitative approach. Data were collected through direct observation of campaign activities, in-depth interviews with the campaign team leader, female campaign team members, female voters, and academics, as well as documentation from official and secondary sources. Data analysis was conducted using Role Theory and Political Recruitment Theory to analyze women’s positions, functions, and involvement in the campaign team.The findings reveal that women perform normative roles as social communicators and community liaisons, as well as actual roles through door-to-door outreach, coordination of campaign activities, and grassroots information gathering. Women are recruited informally through social networks, selected based on loyalty and performance, and developed through practical field experience, with placement largely in operational and communication roles. Although women make significant contributions to expanding campaign reach and building public trust, their access to strategic positions remains constrained by patriarchal culture, gender stereotypes, and role conflict between domestic responsibilities and political engagement.